Brazilian soccer players and no-players adolescents: effect of the maturity status on the physical capacity components performance - Pittoli, Tiago Eduardo Moreira [UNESP]; Barbieri, Fabio Augusto [UNESP]; Pauli, José Rodrigo; Gobbi, Lilian Teresa Bucken [UNESP]; Kokubun, Eduardo [UNESP] (Asociacion Espanola de Analisis del Rendimiento Deportivo, 2010)
The aim of this study was to compare the speed and the agility between Brazilian soccer players and non-players, regarding maturity status in adolescents 11-15 years old. Forty and two soccer players (age – 159.30±17.28 months old; weight – 48.45±9.96 kg; height – 1.53±0.10 m) and 45 non-players (age – 162.62±24.92 months old; weight – 48.30±8.35 kg; height – 1.54±0.12 m) participated of this study. Participants were classified by maturity status. On 2 different days with 1 week of differences between the assessments the participants were evaluated the agility, by Shuttle Run test, and the speed, by 30 m maximum speed test. The results showed that the maturity status was an influential factor in the performance with better results for individuals in a more advanced stage. The soccer practice does not seem to interfere in the performance of the physical capacity components analyzed, only effective when different maturity levels are involved in the analysis. It is also possible that late maturing boys selectively drop-out of soccer as age and sport specialization increase.
Keywords: Soccer; Maturity level; Speed; Agility